Paleosecular Variation of Direction and Intensity from Two Pliocene-Pleistocene Lava Sections in Southwestern Iceland. (Dataset) ... - Tanaka, Hidefumi; Maseru Kono; Shigetoshi Kaneko (Magnetics Information Consortium (MagIC), 2012)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleosecular Variation of Direction and Intensity from Two Pliocene-Pleistocene Lava Sections in Southwestern Iceland. ...